Mutations in the vesicular trafficking protein annexin A11 are associated with amyotrophic lateral sclerosis - Smith, Bradley N. (Sci Transl Med, 2017)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder. We screened 751 familial ALS patient whole-exome sequences and identified six mutations including p.D40G in the ANXA11 gene in 13 individuals. The p.D40G mutation was absent from 70,000 control whole-exome sequences. This mutation segregated with disease in two kindreds and was present in another two unrelated cases (P = 0.0102), and all mutation carriers shared a common founder haplotype. Annexin A11-positive protein aggregates were abundant in spinal cord motor neurons and hippocampal neuronal axons in an ALS patient carrying the p.D40G mutation. Transfected human embryonic kidney cells expressing ANXA11 with the p.D40G mutation and other N-terminal mutations showed altered binding to calcyclin, and the p.R235Q mutant protein formed insoluble aggregates. We conclude that mutations in ANXA11 are associated with ALS and implicate defective intracellular protein trafficking in disease pathogenesis.